Silicon CMOS architecture for a spin-based quantum computer - M. Veldhorst; H. G. J. Eenink; C. H. Yang; A. S. Dzurak (Nature Communications, 2017)
Realisation of large-scale quantum computation requires both error correction capability and a large number of qubits. Here, the authors propose to use a CMOS-compatible architecture featuring a spin qubit surface code and individual qubit control via floating memory gate electrodes.